Geometric modelling and its application to design highways - Levterov, A. I.; Plekhova, H. A.; Kostikova, M. V. (Харківський національний автомобільно-дорожній університет, 2022)
Mathematical models to solve optimization connection problems in nonsimply connected regions under typical technological restrictions on geometric and topological parameters of routes, first of all, on curvature and the number of bends, have been investigated and developed. The models are linked with the extant and prospective topogeodesic models of the polygonal images of territories.
Keywords: mathematical model; optimization problem; restriction; topological parameter; construction norm and rule; homotopy; accuracy; 624